2012
DOI: 10.1111/j.1600-0846.2012.00638.x
|View full text |Cite
|
Sign up to set email alerts
|

Image statistics on the age perception of human skin

Abstract: Our results reveal the importance of higher order statistics for the development of nonintrusive skin quality assessments of the skin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
31
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 17 publications
5
31
0
Order By: Relevance
“…Compared to another investigation on a Russian population with a very similar methodology [14], correlation coefficients of all wrinkles/roughness measurements with age were higher in India, suggesting more severe deterioration of these parameters throughout the ageing process versus Russian skin. Similarly to previous studies involving chronological and perceived aged relationships with skin features, most of the correlation coefficients with perceived age were generally higher than those with chronological age [21,23,27], confirming again that age perception is a critical tool for the understanding of skin ageing.…”
Section: Discussionsupporting
confidence: 81%
“…Compared to another investigation on a Russian population with a very similar methodology [14], correlation coefficients of all wrinkles/roughness measurements with age were higher in India, suggesting more severe deterioration of these parameters throughout the ageing process versus Russian skin. Similarly to previous studies involving chronological and perceived aged relationships with skin features, most of the correlation coefficients with perceived age were generally higher than those with chronological age [21,23,27], confirming again that age perception is a critical tool for the understanding of skin ageing.…”
Section: Discussionsupporting
confidence: 81%
“…The skewness of the luminance histogram is a critical factor in glossiness, freshness perception, and perceived quality [2][3][4][5][6]. Our data suggests that skewness also affects the perception of wood image quality.…”
Section: The Effect Of Skewnessmentioning
confidence: 64%
“…Here, the luminance channel is sensitive to higher spatial frequencies than chromatic channels. Previous studies have shown that the luminance histogram is an effective factor to assess the perceived quality of materials [2][3][4][5][6]. Thus, we focused on the relationship between three parameters: the skewness and kurtosis of the luminance histogram, and the realness values, as shown in Fig.…”
Section: Colorimetric Analysis Of Wood Samplesmentioning
confidence: 99%
See 2 more Smart Citations